Phân tích đa thức thành nhân tử BẰng cách đặt x(x-1)(x+1)(x+2)-3

Question

Phân tích đa thức thành nhân tử BẰng cách đặt
x(x-1)(x+1)(x+2)-3

in progress 0
Gerda 8 tháng 2020-10-17T12:51:41+00:00 2 Answers 118 views 0

Answers ( )

  1. Đáp án:

    x( x-1)(x+1)(x+2)-3

    =x²-x(x+1)(x+2)-3

    =x²-x(x²+2x+x+2)-3

    =x²-x³-2x²-x²-2x-3

    =x(x-x²-2x-x-2)-3

    xin ctlhn

     

  2. Đáp án:

    `(x^2+x-3)(x^2+x+1)`

    Giải thích các bước giải:

     `x(x-1)(x+1)(x+2)-3`

    `=[x(x+1)][(x-1)(x+2)]-3`

    `=(x^2+x)(x^2-x+2x-2)-3`

    `=(x^2+x)(x^2+x-2)-3`

    `=(x^2+x-1+1)(x^2+x-1-1)-3`

    `=(x^2+x-1)^2-1-3`

    `=(x^2+x-1)^2-4`

    `=(x^2+x-1-2)(x^2+x-1+2)`

    `=(x^2+x-3)(x^2+x+1)`

Leave an answer